Insights into nitrogen and boron-co-doped graphene toward high-performance peroxymonosulfate activation : maneuverable N-B bonding configurations and oxidation pathways - Chen, Xiao (2021)
Nitrogen and boron-co-doped graphene was synthesized through two-step thermal annealing (2sNBG) which was employed as a PMS activator to degrade sulfacetamide (SAM). The concentration of the main reactive functionalities (pyridinic N and substitutional B (BC3)) as well as catalytic activity of 2sNBGs were delicately maneuvered through tuning the thermal annealing temperatures. The catalytic performances of the doped graphene in this study followed the order of 2sNBG800 > 2sNBG900 > 2sNBG700 > 2sNBG600 > NG600 > 1sNBGs > BG800. 30.4 at.% N of h-BN (Nh-NB/Ntotal) and 32.8 at.% B of h-BN (Bh-NB/Btotal) were detected in the 1sNBG800, which hampered the catalytic oxidation of SAM via PMS activation by 1sNBG. Among all the 2sNBGs, 2sNBG800 (2sNBG prepared at 800 °C) possessed the highest level of N (13.8 at.%) and B (16.3 at.%), the highest content of pyridinic N (73.4 at.%, Npyridinic-N/Ntotal) and BC3 (43.4 at.%, BBC3/Btotal), the lowest B-C–O (56.6 at.% BC2O, BBC2O/Btotal) content and none of h-BN. 2sNBG800 performed best to activate PMS for catalytic oxidation of SAM. Both radical quenching experiment and DFT calculation revealed that the introduction of B into NG can facilitate the transition from a non-radical oxidation dominating in the NG/PMS system to the coexistence of non-radical and radical oxidation in the 2sNBG/PMS system. The synergistic coupling effect between pyridinic N and BC3 (bonding configuration of B-C-C-C-pyridinic N) was the main reason for the enhanced catalytic activity of 2sNBG800. The transformation of the amine group and subsequent mineralization can effectively minimize the hazardous potentials of sulfonamides to the environment. The SAM degradation was negligibly influenced by NO3− in the 2sNBG800/PMS/SAM system, while Cl− and humic acid led to 33% and 64% decrease in kapp, respectively. The adsorbed intermediates mainly accounted for the deactivation of 2sNBG. This study provides an insight into the function of different N-B bonding configurations in NBG for metal-free catalytic oxidation.